Anger and hostility: are they different? An analytical exploration of facial-expressive differences, and physiological and facial-emotional responses. Issue 3 (2nd April 2020) - Tsikandilakis, Myron; Bali, Persefoni; Derrfuss, Jan; Chapman, Peter
ABSTRACT: Previous research has proposed the exploratory hypotheses that hostility could differ from anger in the sense that it involves higher possibility for inflicting physical harm while anger could involve higher frustration and stress compared to hostility. Based on these hypotheses we tested whether there are expressive differences and discrete emotional responses between angry and hostile faces. We used participant assessment to preselect faces. We found that using action unit analysis, faces labelled as angry and hostile revealed differences in expressive characteristics and that hostile faces were – as predicted – rated by the participants higher for the intent to inflict physical harm. Subsequently, we presented these faces, as well as fearful, sad and neutral faces, overtly and using masking and measured skin-conductance, heart-rate and facial-emotional responses. We found that in both conditions faces expressing hostility led to higher physiological arousal. Detection of a face was a necessary condition for physiological responses to angry and hostile expressions when faces were presented using masking. We found that during overt presentations, hostility elicited fearful facial-emotional responses while anger elicited mirroring responses. Our findings suggest that hostility is a fear-eliciting emotion related to anger with distinguishable expressive characteristics.